2010
DOI: 10.1002/pssc.200983569
|View full text |Cite
|
Sign up to set email alerts
|

Hall mobilities in GaNxAs1‐x

Abstract: In this work we report a systematic study of the electron and hole mobilities of GaNxAs1‐x alloys with different dopants (Zn, Te) and carrier concentrations (1017‐1019 cm‐3). We found a very slight reduction of the hole mobility in p‐GaNxAs1‐x compared to p‐GaAs, indicating that for small N contents (∼1.6%) the valence band is not affected by the N incorporation. In a striking contrast, incorporation of even small amounts of N leads to an abrupt reduction of the electron mobility in n‐GaNxAs1‐x. We further sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Not only the potential fluctua-tion but the electron effective mass was considered to be effected by the arrangement of nitrogen atoms. The potential fluctuation was also considered as a scattering source [14,15]. Fahy et al and Vaughan et al suggested that increasing the density of states due to nitrogen pairs and clusters increased scattering rate [16,17].…”
mentioning
confidence: 99%
“…Not only the potential fluctua-tion but the electron effective mass was considered to be effected by the arrangement of nitrogen atoms. The potential fluctuation was also considered as a scattering source [14,15]. Fahy et al and Vaughan et al suggested that increasing the density of states due to nitrogen pairs and clusters increased scattering rate [16,17].…”
mentioning
confidence: 99%